ڕەگەزی ململانێ لە بنیاتی دەقی شانۆنامەی شیعری (ئۆثیلۆی سپی)دا - حسێن, پ٠ی٠د٠ عطا رشید; حەسەن, پ.ی.د. مەریوان عومەر (Sulaimani Journal for Humanities, 2021)
Conflict, is one of the active and living element of literature ,and more specifically in tales and plays. It is also obvious that play scripts is diverse and each of the artistic structures and elەements have their own places and job inside the script. Obviously , the play scripts are expressed on the basis of their stories in which the element of conflict is an impressive and joyful artistic element of the script for the readers and witnesses. In the play script of white Ovilia, where there are multiple and diverse conflicts ,and the author express the good and the bad through the symbolic characters. In this research , we focused on the role and value of such important elements on this script in which they are expressed by both of the main characters White Ovilia and Black Ovilia. This play script had been written during the 80s of last century by Ariwan Omer Dewlet who was martyred by the Baath Regime in the uprising of 1991. We also used lots of trusted and useful scientific sources of which explain the modern play literature for our research.